2017
DOI: 10.1590/1678-98652017000400010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional care of overweight adults from the perspective of comprehensive health care

Abstract: Objective: Describe and evaluate the nutritional care provided for overweight adults by the Primary and Secondary Health Care services of Santos, São Paulo, Brazil. Methods: This study was carried out between 2013 and 2015 integrating quantitative and qualitative approaches; it was divided into two phases: (1) characterization and (2) evaluation. In phase 1, a census of Primary Health Care Units (n=28) and Secondary Health Care Units (n=4) was conducted using interviews with health service managers and/or hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
1
6
1
5
Order By: Relevance
“…There was no difference in the supply of FNA when there were one or more guidance documents (Food Guide for Brazilian Population, and other technical manuals) in the PHC. A similar finding was presented by Neves, Zangirolani and Medeiros, who showed that the use of technical manuals in PHC in a municipality of São Paulo state was unimportant 31 . The professionals interviewed by these authors emphasized the need for an adequate work space to carry out group activities and to favor multi-professional practice.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…There was no difference in the supply of FNA when there were one or more guidance documents (Food Guide for Brazilian Population, and other technical manuals) in the PHC. A similar finding was presented by Neves, Zangirolani and Medeiros, who showed that the use of technical manuals in PHC in a municipality of São Paulo state was unimportant 31 . The professionals interviewed by these authors emphasized the need for an adequate work space to carry out group activities and to favor multi-professional practice.…”
Section: Discussionsupporting
confidence: 84%
“…The professionals interviewed by these authors emphasized the need for an adequate work space to carry out group activities and to favor multi-professional practice. However, the current study found no influence of the PHC´s infrastructure, such as waiting room, yard, patio and/or attendance room in the provision of FNA 31 .…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Os processos de trabalho e as possibilidades de atuação interdisciplinar para o cuidado integral nas diferentes fases da vida, além da articulação de redes, constituem os aspectos mais frágeis e que necessitam ser enfrentados pela equipe de saúde para atender aos preceitos de integralidade na atenção à saúde no Brasil. 2,4,10,11 O nutricionista, inserido na equipe multiprofissional na Atenção Primária à Saúde, possui competências e atribuições para atuar em diferentes frentes de ação, de caráter universal e específico. 7,12 A formação deste profissional é a base para o direcionamento e o desempenho profissional na área de Saúde Coletiva.…”
Section: Introductionunclassified